THE EFFECT OF ARTICULATION LEARNING MODELS ON STUDENTS’ UNDERSTANDING IN THE REPUBLIC INDONESIA PROCLAMATION OF INDEPENDENCE MATERIALS AT 5th GRADE OF ELEMENTARY SCHOOL IN SOCIAL STUDIES - Santa Santa; Wawan Syahril Anwar; Roni Sukmawan (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2019)
Abstrak. This study aims to determine the effect of articulation learning models on students' understanding The Republic Indonesia proclamation of independence materials at 5th grade in social studies subjects. The method that used in this research is a quasi experiment with the design of Nonequivalent (Pre-Test and Test Post) Control- Group Design. The design of the Group-Control Design is Non-equivalent Pre-Test and Post Control Group Design Test. The subjects of this research were the 5th grade students of SDN Babakan, Bogor City, with Academic Year of 2016/2017. The results of this research are obtained data on the average pretest score of the experimental group is 56.80 and control group is 56.60. The average differences in the pretest scores of the experimental and control group are obtained by a significance value of 0.812> 0.05, so H0 was accepted. It can be concluded that there is no difference in the pretest scores of the experimental group and the control group. The average final score of the post-test experimental group was 89, the control group was 68.29. The different test of the average post-test score of experimental and control group in the both populations is if the significance score (P-value) > α, with the significance score is 0,000 ≤ 0.05. then H0 is rejected and H1 is accepted. This can be concluded that there are differences in the average post-test score in experimental group and control group. The conclusion of the obtained data is that the articulation learning model in the experimental group can influence the understanding of elementary students about Republic Indonesia proclamation of independence materials. Keywords: articulation, student understanding, social studies learning